2016
DOI: 10.1021/acs.jpclett.6b02320
|View full text |Cite
|
Sign up to set email alerts
|

Slow Singlet Fission Observed in a Polycrystalline Perylenediimide Thin Film

Abstract: Singlet exciton fission (SF) is a process wherein an exciton in an organic semiconductor divides its energy to form two excitations. This process can offset thermalization losses in light harvesting technologies, but requires photostable materials with high SF efficiency. We report ultrafast kinetics of polycrystalline films of N-N'-dioctyl-3,4,9,10-perylenedicarboximide (C8-PDI), a chromophore predicted to undergo SF on picosecond time scales. While transient absorption measurements display picosecond dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
145
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(161 citation statements)
references
References 80 publications
15
145
1
Order By: Relevance
“…Therefore, the ratio of second‐order decay constants provides a direct measure of the relative diffusion constants for triplet transfer within the SA and TA films. [11a,13]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the ratio of second‐order decay constants provides a direct measure of the relative diffusion constants for triplet transfer within the SA and TA films. [11a,13]…”
Section: Resultsmentioning
confidence: 99%
“…However, the surge in interest in SF over the past 5 years has led to a dramatic increase in the number of chromophores known to undergo SF, with newly synthesised materials being added to the list all the time. It has been suggested that several polyacenes/polyacene dimers 11,[51][52][53] , PDIs 32,54,55 , terrylenes/TDIs 27,56 and CT-polymers 57 undergo efficient fission. Some of these molecules fulfil many of the above criteria, but none can fulfil all of them.…”
Section: B Chromophore Packingmentioning
confidence: 99%
“…Singlet fission is a possible contributor to the reduction. [22][23][24][25] Since the emitter concentration must be much lower than the sensitizer concentration to produce a low self-absorption device, emitter self-aggregation effects are less important to solar concentrator design.…”
Section: H-type Aggregationmentioning
confidence: 99%